2020
DOI: 10.1016/j.jamcollsurg.2019.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Imaging of Pancreatic Cysts and Cyst-Associated Pancreatic Cancer in BRCA1/2 Mutation Carriers: A Retrospective Cross-Sectional Study

Abstract: BACKGROUND: Direct-to-consumer BRCA testing will increase BRCA diagnoses and subsequent abdominal imaging. It is unclear whether BRCA carriers are at higher risk of developing pancreatic cysts (PCs) or cyst-associated pancreatic ductal adenocarcinoma (PDAC). We investigated the prevalence of PCs in BRCA-tested patients, and whether BRCA-carriers have higher rates of PDAC when PCs are found. STUDY DESIGN: This is a retrospective cross-sectional study of patients with BRCA testing and abdominal imaging between 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…The lifetime risk of PDAC is about 1% for BRCA1 and 4.9% for BRCA2 PV/LPVs carriers [ 30 ], and studies by the Breast Cancer Linkage Consortium reported a 2.3-fold and 3.5-fold increased risk of PDAC in carriers of BRCA1- and BRCA2 -altered variants, respectively [ 14 ]. In addition, a few studies analyzed the prevalence and clinical features of pancreatic cystic lesions in a BRCA -tested population in order to establish the risk of pancreatic cysts and cyst-associated cancer, which could have important implications in the context of increasingly accessible genetic testing [ 31 , 32 , 33 ], but there were significant limitations. The use of next-generation-sequencing (NGS)-based technologies is becoming a new gold standard for determining molecular predictive biomarkers and reliable data on the detection of multiple pathogenic variants, allowing for the screening of thousands of affected individuals [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lifetime risk of PDAC is about 1% for BRCA1 and 4.9% for BRCA2 PV/LPVs carriers [ 30 ], and studies by the Breast Cancer Linkage Consortium reported a 2.3-fold and 3.5-fold increased risk of PDAC in carriers of BRCA1- and BRCA2 -altered variants, respectively [ 14 ]. In addition, a few studies analyzed the prevalence and clinical features of pancreatic cystic lesions in a BRCA -tested population in order to establish the risk of pancreatic cysts and cyst-associated cancer, which could have important implications in the context of increasingly accessible genetic testing [ 31 , 32 , 33 ], but there were significant limitations. The use of next-generation-sequencing (NGS)-based technologies is becoming a new gold standard for determining molecular predictive biomarkers and reliable data on the detection of multiple pathogenic variants, allowing for the screening of thousands of affected individuals [ 34 ].…”
Section: Discussionmentioning
confidence: 99%